On the Characteristics of Nomadic Expressions in Contemporary Mongolian Literature - Tsedenpil, Tsevelmaa (Mongolian Language and Literature Studies, 2025)
The 1990s were a special period in the development of contemporary Mongolian prose poetry, for example, the literary movements in Mongolian poetry were from oral to written literature; from meditation to realism; from realism to postmodernism; from oriental tradition to Russian and European literature; and from classic nomadic culture to urban culture. Moreover, this period was a special time of literature reform when literary criticism was founded as a separate field to study prose poems. In this article, we aim to illustrate and analyze the unique imagery and cultural expressions found in the literary works of B. Lkhagvasuren, who holds the titles “People’s Writer”. For instance, in his poetic descriptions of the traditional Mongolian dwelling, the ger Lkhagvasuren employs symbolic methods that reflect the distinctive worldview of the Mongolian people. Through depictions rooted in the everyday life of nomads, he conveys fundamental aspects of Mongolian culture and customs. These include the structure of the ger, the domestic craftsmanship of Mongolian women, the sacred bond between mother and child, solar time, cardinal directions, and numerological symbolism. Монголын орчин үеийн уран зохиол дахь нүүдэлчдийн үг хэллэгийн онцлогоос Хураангуй: Монголчууд аман болон бичгийн соёлын асар их өв уламжлалтай ард түмэн билээ. Эдүгээ бидний үе хүртэл хөгжиж ирсэн бичгийн уран зохиолын мянга гаруй жилийн түүхэнд яруу найраг нь нийгэм, соёлын өөрчлөлт шинэчлэлтийг хамгийн түрүүн тусгаж ирсэн уламжлалтай. Нүүдлийн соёл иргэншилт монголчуудын бусад улс үндэстнээс ялгарах ондоошил нь тэдний эрхэлж буй мал аж ахуй, байгаль экологийн унаган төрх байдал, өдөр тутмын ахуй амьдралтай нягт уялдаа холбоотой бөгөөд эдгээрийг илэрхийлсэн онцлог үг хэллэгтэй байдаг. Иймд энэхүү өгүүлэлдээ бид “Ардын уран зохиолч” Б.Лхагвасүрэнгийн уран бүтээл дэх нүүдэлчдийн үг хэллэгийн тухай, энэ нь хэлний дархлаанд хэрхэн нөлөөлөх тухай товч судлахыг хичээлээ. Түлхүүр үгс: Орчин үеийн уран зохиол, “Ардын уран зохиолч”, соёл түүх, зан заншил, өвөрмөц онцлог